Production of Low-cost Lactic Acid from Dairy Wastes and Dates Wastewater and Bioactive Silver-Poly (Lactic Acid) Nanocomposite for Biological Applications - Muthumareeswaran Muthuramamoorthy; Ali Aldalbahi; Khwater Mishaal Radi Alanzi; Saravanan Pandiaraj; Ponmurugan Karuppiah; Periyasami Govindasami (BioResources, 2024)
L-Lactic acid-producing Lactobacillus lactis and L. plantarum were isolated from date wastes. The fermentation process was optimized using a one-variable-at-a-time approach. Dairy wastewater and wastewater from the date industry were utilized as low-cost culture media to produce lactic acid. The selected two bacterial strains were co-cultured in wastewater medium to produce L-lactic acid and D-lactic acid. Lactic acid production was significantly improved by glucose (carbon source), yeast extract (nitrogen source), initial inoculum level, and polysorbate 80. A central composite design and response surface methodology were used to optimize the variables and their levels to improve lactic acid yield. The supplemented yeast extract, glucose, and polysorbate 80 improved lactic acid. The predicted variables and their levels for maximum lactic acid production were glucose (67.5 g/L), yeast extract (10.28 g/L), and polysorbate 80 (0.48 mL/L). The prepared nanocomposites exhibited antibacterial activity against foodborne bacterial pathogens. The structural properties of the silver-polylactic acid nano compost materials were determined. The characterized compost materials exhibited a peak absorption wavelength of 430 nm. The silver and poly(lactic acid) were characterized using X-ray diffraction analysis and were 30 to 50 nm in size.